Antifungal Susceptibility Survey of 2,000 Bloodstream Candida Isolates in the United States - Ostrosky-Zeichner, Luis (American Society for Microbiology, 2003)
Candida bloodstream isolates (n = 2,000) from two multicenter clinical trials carried out by the National Institute of Allergy and Infectious Diseases Mycoses Study Group between 1995 and 1999 were tested against amphotericin B (AMB), flucytosine (5FC), fluconazole (FLU), itraconazole (ITR), voriconazole (VOR), posaconazole (POS), caspofungin (CFG), micafungin (MFG), and anidulafungin (AFG) using the NCCLS M27-A2 microdilution method. All drugs were tested in the NCCLS-specified RPMI 1640 medium except for AMB, which was tested in antibiotic medium 3. A sample of isolates was also tested in RPMI 1640 supplemented to 2% glucose and by using the diluent polyethylene glycol (PEG) in lieu of dimethyl sulfoxide for those drugs insoluble in water. Glucose supplementation tended to elevate the MIC, whereas using PEG tended to decrease the MIC. Trailing growth occurred frequently with azoles. Isolates were generally susceptible to AMB, 5FC, and FLU. Rates of resistance to ITR approached 20%. Although no established interpretative breakpoints are available for the candins (CFG, MFG, and AFG) and the new azoles (VOR and POS), they all exhibited excellent antifungal activity, even for those strains resistant to the other aforementioned agents.